1.Wyznacz ze wzoru wybraną wielkość:
a)F=ma,a
b)E=mgh,h
c)P=F/S,F
d)P=W/t,t
e)E=mv2(kwadrat)/2,m
f)F=mv2(k)/r,r
g)a=v1-v2/t,v1
h)a=v1-v2/t,t
i)Q=mc(T2-T1),T2

2.Rozwiąż układy równań (metodą przeciwnych współczynników):
a)3x-2y=5
-2x-6y=9

b)3-3x=3y+2
y+5=4x-3

c)-7=5x-3y
3y-5x=0

d)6x=10-4y
2-2/5y-3/5x=0

e)-2(5x-2y)+4(2x=y)=1
3(2x-y)-(y+7x)=5,5

f)(x=3)2(k)-(y-1)2(k)=(x-y)(x+y)
3x-7y=0

g)(x-5)2-(x+2)2=7y
(y+4)2-(y-2)(y+2)=8x

1

Odpowiedzi

2010-03-21T13:20:16+01:00
1. a)F=ma /:m
F/m= a

b) E=mgh /:mg
h= E/mg

c)P=F/S /*S
F= P*S

d)P=W/t /*t
Pt= W /:P
t=W/P

e)E=mv2(kwadrat)/2 /:v2(kwadrat)
m= E/v2(kwadrat)

f)F=mv2(k)/r /*r
r*F=mv2(k) /:F
r= mv2(k) /F

g)a=v1-v2/t /*t
at= v1-v2
at+v2=v1

h)a=v1-v2/t /*t
at= v1-v2 /:a
t= (v1-v2)/a

i)Q=mc(T2-T1) /:mc
Q/mc= T2-T1
Q/mc+T1= T2


2.a)3x-2y=5 /*(-3)
-2x-6y=9

-9x+6y=-15
-2x-6y=9
dodajemy
-11x= -6 /: -11
x= 6/11

3* 6/11 - 2y =5
18/11 -2y =5
-2y= 5 - 18/11
-2y = 55/11 - 18/11
-2y= 37/11 /:(-2)
y = -37/22

b)3-3x=3y+2
y+5=4x-3

-3x-3y=-1
-4x+y= -8 /*3

-3x-3y=-1
-12x+3y=-24

-15x=-25 /:(-15)
x= 5/3

-3*5/3-3y=-1
-5 - 3y=-1
-3y= 4 /:(-3)
y= - 4/3

c)-7=5x-3y
3y-5x=0

5x-3y= -7
-5x+3y=0
0=0
układ sprzeczny

d)6x=10-4y
2-2/5y-3/5x=0 /*10

6x+4y=10
20 -4y-6x=0
0=0
ukl. sprzeczny

e)-2(5x-2y)+4(2x=y)=1
3(2x-y)-(y+7x)=5,5

-10x + 4y +8x+4y=1
6x-3y-y-7x=5,5

-2x+8y=1
-x-4y=5,5 /* (-2)

-2x+8y=1
2x+8y=11
16y= 12 /:16
y=3/4

-2x+8*3/4=1
-2x+6 = 1
-2x=5 /:-2
x= -5/2

f)(x=3)2(k)-(y-1)2(k)=(x-y)(x+y)
3x-7y=0

x^2+6x+9 - y^2 +2y - 1 = x^2 -y^2
3x-7y=0

6x+2y= -8
3x-7y=0 /*-2

6x+2y= -8
-6x +14y =0

16y= -8 / 16
y=-1/8

3x-7*(-1/8)=0
3x= -7/8 /:3
x=-7/24



g)(x-5)2-(x+2)2=7y
(y+4)2-(y-2)(y+2)=8x

x^2 - 10x +25 - x^2 -4x - 4 = 7y
y^2+8y+16 -y^2 +4 =8x

-14x -7y= -21 /:-7
-8x +8y=-20 /:4

2x+y=3
-2x+2y=-5

3y= -2 /:3
y=-2/3

2x-2/3 =3
2x=3 + 2/3
2x = 11/3 /:2
x= 11/6